Char-supported nickel and cobalt catalysts for the steam reforming of tar / Farah Aimi Fuadi - Fuadi, Farah Aimi (2016)
The formation of tar is a major problem in the biomass gasification process since it can disrupt downstream process operations. One of the approaches used to address this problem is by nickel-based catalysts for tar removal. However, these catalysts are negated by the fact that they are pose waste disposal problems. Hence, an alternative approach for tar removal is to use the char as catalyst support. To date, little is known on the catalytic steam reforming performance of char-supported nickel and cobalt catalysts for tar removal. Therefore, the main objective of this research is to investigate the catalytic performance of char-supported nickel and cobalt catalysts on steam reforming of toluene, whereby the chars used as catalyst supports are derived from different types of biomass available in Malaysia. In order to achieve the objective above, the adsorption capacity of nickel and cobalt ions in four types of biomass is first investigated, comprising oil palm mesocarp fibres (OPMF), empty fruit bunches (EFB), palm kernel shells (PKS) and sawdust. The metal-loaded biomass are characterised using FTIR and ICP-OES. The biomass having the lowest and the highest metal adsorption capacity are chosen to prepare the char-supported catalysts in order to determine the effect of char precursor on the catalytic steam reforming performance of toluene. The char-supported catalysts are characterised by ICP-OES, N₂ adsorption surface analysis, FESEM, and ultimate and proximate analysis. The effect of temperature on the catalytic steam reforming performance of toluene is studied within a temperature range of 700-950 °C. It is found that the possible mechanism for metal adsorption on biomass is ion exchange, which can be observed from the changes of the -OH group in the FTIR metal-loaded char spectra. The order of metal adsorption capacity as followed: OPMF>sawdust>EFB>PKS. Carbonisation and steam activation of the biomass results in a large surface area, which then contribute to the higher contact between the catalysts and the tar compound. . Carbonisation and steam activation produced high surface area 206 to 277 m²/g. The cobalt catalyst exhibits higher catalytic activity compared to the nickel-supported catalyst. The concentration of syngas increases up to 45% with an increase in temperature from 700 to 850 °C. After 850 °C, the catalytic activity of the catalysts begins to decrease, which may be due to carbon deposition and thermal sintering.